(untitled) (Studia theodisca, 2013)
In his essayistic novel Spiegelland. Ein deutsches Monolog (1992), Kurt Drawert engages in an intense criticism of the dictatorship in the former DDR, at fault for having reduced language to a tool for the control of conscience. This article seeks to demonstrate how Drawert’s criticism concerns not only the sphere of language, but also the sphere of the visual. Thus photography, for example, is affected in the same way as language by that “illusion of representation” in which the subject is caged. This article also seeks to show how Drawert’s language and image criticism is inspired by aspects of Lacan’s and Wittgenstein’s lines of thought.